Advancing Machine Learning Methods for Small and Large Biological Datasets: Applications in Redox Potential Prediction, Enzyme Interaction Prediction, and Spectra Annotation - Kalia, Apurva. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Computer Science.; Advisor: Soha Hassoun.; Committee: Liping Liu, Remco Chang, Sameer Sonkusale, and Dilip Krishnan.; Keywords: Computer science, Artificial intelligence, and Bioinformatics.